ACADEMIC FACULTIES AND STUDENT AFFAIRS SUBDIVISION COLLABORATE TO ENSURE SUSTAINED STUDENT SATISFACTION AND ENHANCED STUDENT SUCCESS: A CASE STUDY OF THE CENTRAL UNIVERSITY OF TECHNOLOGY FS - Titus Williams (PUPIL: International Journal of Teaching, Education and Learning, 2025)
South African institutions of higher learning are prone to student protest and mass demonstrations and at the core of these is related to the service render to them during their study period. Aggrieved students always justify their anarchy and burning of university property to lack of service delivery or poor service delivery. This resulted in sporadic protest actions across institutions of higher learning in South Africa. This prompted the need for higher education institutions and government to do reflection on the services they provided to students. The need for efforts by front-face offices e.g. academic faculties and student affairs offices to find strategies to collaborate and find solutions to avoid anarchy and destruction by protesting students. This paper examines the significance of collaboration between academic faculties and student affairs in ensuring efficient service delivery to students. Primary qualitative data collected using semi-structured interviews with random students who visited both the academic faculty of Humanities and the student affairs offices to register their student and academic related challenges. The paper identifies the challenges faced by academic faculties and student affairs in working together and develop strategies that can be employed to overcome these challenges. A qualitative data collection method is explored by using semi-structured interviews with a sample of 58 students in the academic faculty of Humanities and 8 Student Representative Council (SRC) members at Central University of Technology Free State in South Africa. This paper explores the development of strategies that will ensure sustained student satisfaction and highlights the benefits of effective collaboration between these two sections, including improved student retention rates, sustained student satisfaction, improved student success and enhanced institutional reputations.